2017
DOI: 10.1039/c7ra07854d
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of high-performance Fe-doped Ce–Mn/TiO2 catalysts for the low-temperature selective catalytic reduction of NOx with NH3

Abstract: A Ce-Mn-Fe/TiO 2 catalyst has been successfully prepared using a single impregnation method, and excellent low-temperature NH 3 -SCR activity was demonstrated in comparison with other typical SCR catalysts including Mn-Ce/TiO 2 and metal-doped Mn-Ce/TiO 2 . The crystal structure, morphology, textural properties, valence state of the metals, acidity and redox properties of the novel catalyst were investigated comprehensively by X-ray diffraction (XRD), N 2 adsorption and desorption analysis, X-ray photoelectron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…This is due to the increase of oxygen mobility on the surface of the catalyst caused by the transformation of Ce 4+ / Ce 3+ . It was also reported that Ce performs excellently in enhancing the oxygen storage capacity of the catalyst and improves the redox activity . According to the H 2 ‐TPR profiles of Fe 2 O 3 based catalysts in Figure , the introduction of CeO x promotes the starting reduction temperature shifting to low temperature.…”
Section: Resultsmentioning
confidence: 89%
“…This is due to the increase of oxygen mobility on the surface of the catalyst caused by the transformation of Ce 4+ / Ce 3+ . It was also reported that Ce performs excellently in enhancing the oxygen storage capacity of the catalyst and improves the redox activity . According to the H 2 ‐TPR profiles of Fe 2 O 3 based catalysts in Figure , the introduction of CeO x promotes the starting reduction temperature shifting to low temperature.…”
Section: Resultsmentioning
confidence: 89%
“…No bands corresponding to La and K were observed in the XRD patterns. This result showed that the promoters (K, La, and Ti) are in the form of small particles and greatly dispersed on the catalyst surface, decreasing the crystallization degree .…”
Section: Resultsmentioning
confidence: 95%
“…More specifically, it could be demonstrated that Ce modified Mn-Ce/TiO2-PILC catalyst enhanced the dispersion of Mn on the surface. Compared with CeO2-MnOx catalyst, the resistance to H2O and SO2 of the Ce-Mn/TiO2 catalyst has been enhanced to some extent [77]. CeO2 can significantly inhibit the deposition of (NH4)2SO4 and NH4HSO4 on the catalyst surface, which is the fundamental reason for the improvement of SO2/H2O resistance [78].…”
Section: Ce-mn/tio 2 Catalystmentioning
confidence: 99%